Does the Circle of Friends intervention have a positive impact on the social inclusion and happiness of children with a hearing impairment? - Paxton, C. (2016)
If children do not experience social inclusion, this can have a negative impact, both in the short- and long-term, such as aggression, poor academic attainment, reduced social skills and psychopathological symptoms. The causes of social exclusion are complex and incorporate many factors, including aggressiveness, shyness and social competence, and the influence of peers. Children with a hearing impairment (HI) have been shown to be at risk of difficulties with social skills. This study evaluates the effectiveness of Circle of Friends (CoF – Newton & Wilson, 2003), a peer support intervention, in improving the social inclusion of four children with a HI who were identified as having issues with social inclusion and friendships by Teachers of the Deaf. The multiple-baseline AB single-case experimental design utilised sociometric data, and was supported by pre-post measures of the children’s happiness and social, emotional and behavioural adjustment. Findings indicate that CoF had some impact on the peer acceptance for all pupils. There was moderate evidence for one pupil, a change in composite score for another, and positive trends for the other two pupils. There appeared to be a small impact on ratings of pro-social behaviours for two of the pupils. There was an improvement (reduction) on one of the pupil’s ‘neutral’ ratings, but no impact on pupils’ ‘unsure’ ratings. There was variable evidence to suggest an impact on peer rejection or adult ratings of behaviour difficulties. There was strong evidence to indicate an improvement for one pupil, moderate evidence for another and none for a third. The final pupil’s peer rejection had a negative trend. The CoF did not improve happiness scores or adult ratings of pupils’ emotional distress. Findings are discussed in relation to relevant literature. Methodological issues and ethical concerns are discussed, and implications for future practice and research are considered.